Incomplete Currarino Syndrome: Case Report and a Brief Review of Literature - Muhammad Abdelhafez Mahmoudand Ashraf Hamed Seddek (Archives of Clinical Gastroenterology - Peertechz Publications, 2020)
Currarino Syndrome (CS) or triad is rare entity that was first reported by Currarino in 1981 as a pathology involving three anomalies; anorectal malformation, a sacral bony defect and a presacral mass. CS can be familial or sporadic, with an autosomal dominant inheritance mode. The English literature reported over 310 cases of Currarino triad with the cases diversity in age, clinical presentation, and management.  Herein, we present a case of neonate with incomplete CS (presacral mass [Sacrococcygeal Teratoma SCT] and low anorectal malformation with normal sacrum). He was diagnosed antenatally. He was full term, weighing 3250 gm and delivered by Caeserian section. He was operated on the second day of life. According to Altman's classification, the case had type II SCT (mainly external with small intrapelvic component). The sacrococcygeal teratomatous mass was about 13×9×10 cm in diameter and weights about 950 gm. He underwent combined abdominal/posterior sacral approach. He underwent diverting colostomy via abdominal exploration & complete excision of the sacrococcygeal mass together with the coccyx through chevron posterior approach, and finally anorectoplasty was done all in the same setting. Colostomy was closed 4 months later and tumor marker turned normal and the child has grown well and led a normal life with accepted continence with no recurrence after 4.8 years of follow up.